The Wedgworth Leadership Institute for Agriculture and Natural Resources - Hannah Carter; Rochelle Strickland (EDIS, 2012)
The Wedgworth Leadership Institute for Agriculture and Natural Resources (WLIANR) develops and refines the leadership capabilities of leaders involved in Florida agriculture and natural resources. These leaders are prepared to become increasingly involved in forming policies that affect the future of Florida agriculture and natural resources in a direct or indirect manner. This 2-page fact sheet was written by Hannah Carter and Rochelle Strickland, and published by the UF Department of Agricultural Education and Communication, October 2012.